Pendampingan Digitalisasi Data Kesehatan Balita Dan Ibu Hamil Berbasis Komunitas - Rina Anggraini; Rani Darma Sakti Tanjung; Febri Aulia (STIKES Columbia Asia Medan, 2025)
The development of information technology offers great opportunities to improve public health services, particularly in managing health data for pregnant women and toddlers. However, at the community level, challenges remain such as manual recordkeeping, limited digital literacy, and the absence of integrated data systems. This community-based digital health data mentoring program aims to enhance the capacity of local cadres and residents to manage health data digitally, accurately, and sustainably. The methods included socialization sessions, training on health data recording applications, and field mentoring over a three-month period in community health posts. The results showed a significant improvement in cadres’ ability to use digital applications (from 45% to 90%) and a 60% reduction in data reporting time. Moreover, the quality of health data collected became more valid and easily accessible to medical staff and local health centers. This program has proven effective in fostering community independence in technology-based health data management and has the potential to be replicated in other regions with cross-sectoral support.